New curcumin-derived ligands and their affinity towards Ga3+, Fe3+ and Cu2+: spectroscopic studies on complex formation and stability in solution. (22nd March 2018) - Rigamonti, Luca; Orteca, Giulia; Asti, Mattia; Basile, Valentina; Imbriano, Carol; Saladini, Monica; Ferrari, Erika
Abstract : Chemico-physical properties, metal chelating ability, antiproliferative activity and DNA binding of new curcuminoids with improved stability. Abstract : The metal complexing ability in solution of four substituted curcumin (CUR )-derived ligandsK3T, originated by the insertion of the –CH2 CH2 COO t Bu branch on the central atom of the diketonic moiety ofCUR and related derivatives with variable meta and para substituents (OH, OMe, H, OCOCH3 ) on the peripheral aromatic rings, is examined. These molecules can act as new chelators with biological properties comparable to those ofCUR but with improved stability. In fact, curcuminoids represent new perspectives for the development of novel therapeutic agents for several diseases including Alzheimer's disease.CUR showed neuroprotective properties, and a probable mechanism of its action is related to the complexation ability towards endogenous metal ions Fe 3+ and Cu 2+ .K3T derivatives retain the solvent-dependent diketo–ketoenol tautomerism, with the prevalence of the diketonic form in aqueous solution. They show enhanced stability in simulated physiological conditions (phosphate buffered solution at pH = 7.4) compared toCUR, together with similar or even higher anti-proliferative activity against human colon carcinoma cells HCT116. The addition of the metal ion causes dissociation of the enolic proton creating chelate complexes and shift of the tautomeric equilibrium toward the keto–enol species. The formation of metal complexes was followed and confirmed by both NMR (using Ga 3+ as a diamagnetic probe for Fe 3+ ) and UV-visible spectroscopy. All the ligands showed high affinity for Fe 3+ and Ga 3+, forming M : L 1 : 2 species. In view of therapeutic applications, notable is the good affinity ofK3T31, i.e. the ligand bearing only OH groups in para positions of the aromatic rings, for Cu 2+, and the ability of the Cu : K3T31 1 : 1 complex to bind to DNA.